The satisfaction level among patients, staff and visitors towards the facilities management in healthcare sector / Nur Shahira binti Izani and Nor Nazihah Chuweni - Izani, Nur Shahira; Chuweni, Nor Nazihah (2019)
Nowadays, the increasing number of population in Malaysia lead to a need of better facility in the public hospitals. Therefore, this study aims to investigate the satisfaction level of patients, staff and visitors towards the facility management in the healthcare sector and the ways to overcome the shortage of such facilities. This study incorporates mixed methods based on quantitative and qualitative method to address the research questions. Data collected via questionnaires from 100 respondents at Hospital Seri Manjung in Perak, Hospital Tengku Ampuan Rahimah (HTAR) in Klang and Hospital Sungai Bakap in Pulau Pinang. Meanwhile, interviews have been conducted with two facility managers from public hospitals to identify the main issue in the facility management. From the interviews, the main issue that caused the lack of facilities is financial problem. So, necessary budget for maintenance need to be prepared to ensure smooth operation and to overcome the shortage of facilities in the government hospitals. As facility manager, they need to plan the given budget and priorities what is important and ensure well-spent expenditure.